Phrenic nerve injury during right inferior pulmonary vein ablation with the second-generation cryoballoon: clinical, procedural, and anatomical characteristics. Issue 10 (22nd November 2017) - Abugattas, Juan-Pablo; de Asmundis, Carlo; Iacopino, Saverio; Salghetti, Francesca; Takarada, Ken; Coutiño, Hugo-Enrique; Ströker, Erwin; De Regibus, Valentina; de Greef, Yves; Brugada, Pedro; Sieira, Juan; Chierchia, Gian-Battista
Abstract: Aims: There is still sparse information regarding phrenic nerve injury (PNI) during ablation of the right inferior pulmonary vein (RIPV) by means of the second-generation cryoballoon advance (CB-A). The aim of this study was to describe the procedural, anatomical, and clinical characteristics of patients who experienced PNI during the RIPV ablation. Methods and results: Consecutive patients who had undergone pulmonary vein isolation (PVI) using CB-A and suffered PNI during RIPV ablation were retrospectively included in our study. A cohort of patients who did not suffer any PNI was randomly included in a 1:3 ratio as a control group. The incidence of PNI during RIPV cryoapplication was 3.5%, (34 of 979 patients). There were no significant differences in clinical characteristics between patients with and without PNI. The prevalence of right common ostium (RCO) was significantly higher in patients with a PNI [4 patients (11.8%) vs. 1 patient (1.0%); P  < 0.01]. A temperature drop velocity from the basal temperature to − 20 °C of 2.38 °C/s rendered a sensitivity of 82.4% and a specificity of 51.0% with a negative predictive value of 89.7%. Temperature drop velocity from basal to − 20 °C and the presence of an RCO were predictors of PNI in the multivariate analysis [odds ratio (OR) 7.27, 95% confidence interval (CI) 2.54–20.80; P  < 0.01 and OR 18.41, 95%CI 1.87–181.23; P  = 0.01, respectively). Conclusion: PNI during RIPV freeze might occur in around 3.5% of cases. The presence of an RCO and a fast temperature drop must prompt a careful monitoring of the phrenic nerve function during cryoapplications on the RIPV.